G341(P) 10-year allograft histology and biopsychosocial health 20 years after paediatric liver transplantation. (25th October 2020) - Vimalesvaran, S; Nevus, L; Deheragoda, M; Samyn, M; Melendez, HV; Heaton, N; Dhawan, A
Abstract : Aims: Survival 20-years after paediatric liver transplantation is >80%. A correlation of this success is that long-term complications are becoming more evident. The aim of this study was to evaluate the long-term medical and psychosocial outcomes of paediatric post-liver transplant patients. Methods: Cohort study of paediatric liver transplant patients in a tertiary UK transplant centre, between 1985 and 2004. Patients surviving to 10-years post-transplantation with normal liver biochemistry were included. Demographic data including indications for transplantation and complication rates were collected. All children underwent protocol liver biopsy at 10-years. Electronic case notes were reviewed for long-term physical and psychosocial outcomes. Results: 84 patients survived to 10 years post-transplant. Median age at transplantation was 1.3 years, with median duration of follow-up of 20.2 years. Most common indication for liver transplantation was extrahepatic biliary atresia (51.2%). Mortality rate after 10 years was 2%. The observed acute and chronic rejection rates were 33.3% and 21.4%, respectively. A significant proportion (66.7%) of children demonstrated mild graft fibrosis at 10-years, despite having normal liver biochemistry. Long-term psychosocial consequences were significant. Roughly 26% of children had emotional and behavioral problems – depression and anxiety being the commonest. Higher rates of psychosocial disorders (35.7%, p=0.59) were seen in patients who required re-transplantation. Substance abuse including smoking and heavy alcohol consumption was lower than the national average – 9.5% and 3.6% respectively. Education and employment rates were comparable to the national average – 38% and 27%, respectively. In our cohort, 31% were in transition clinics. We report 23% with chronic renal dysfunction 20-years post-transplantation, on standard immunosuppression regimens. eGFR values were calculated using cystatin-C values. Only 3 patients had a BMI of >30, with a mean BMI of 20.4 in our cohort. Conclusion: Whilst survival is excellent at 20 years, there is an emergent long-term impact of transplantation. Liver histology was abnormal in a significant proportion of our cohort despite normal liver biochemistry. Our findings demonstrate the importance of assessing physical health, specifically with regard to renal function and growth, as these children transition to adult services. The overarching impact of transplantation on the psychosocial wellbeing of survivors should form a key part of assessment post-transplantation.